The Relations Between Diabetes Mellitus Type 2 on The Incidence Cataract in Balai Kesehatan Mata Makassar in 2016 - Amaliah, A. Nurul; Febriza, Ami (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2019)
The aim of this research was to know about the correlation between cataract occurance with Diabetes Mellitus. This research was performed in Medical Record Departement of Balai Kesehatan Mata Masyarakat Makassar using medical record on the period of January 2016 to October 2016 with case control design, consist of 74 subjects which were divided into cataract as case, consist of 37 subjects and without cataract as control, consist of 37 subjects. Data of diabetes mellitus history were collected from patient medical record and analyzed by Chi Square with the significance’s degree was p<0.05. The result showed moderate correlation between cataract occurance and diabetes mellitus (p=0.002) with Odds Ratio (OR) 4,563 (IC :1,683 – 12,371)